Conflict and contract law - MacMahon, Paul H. (Oxford journal of legal studies, 2018)
This article examines an under-explored reason to have contract law: conflict minimization. An important function of contract law, the article contends, is to diminish the wasted time, effort, and resources spent on disputes over economic exchange, and to reduce the incidence of harm resulting from these disputes. Minimizing conflict typically serves the parties’ own interests, and it also serves the public interest in social peace. These insights have implications not just for contract law as a whole but also for its doctrinal details. The article thus discusses how several doctrines of substantive contract law help to minimize conflict, without claiming that currently prevailing contract law regimes are perfectly adapted to this aim. Finally, it defends the normative claim that conflict minimization should be considered one of contract law’s goals